Multifactorial analysis of factors influencing premolar mobility in stage III/IV grade C periodontitis patients ≤ 35 years of age: a cross-sectional study - Jia-Ming Li; Xian-E Wang; Xiao Xu; Jian Liu; Li Zhang; Xiang-Hui Feng; Rui-Fang Lu; Li Xu; Huan-Xin Meng (BMC, 2024)
Abstract Background Previous studies have suggested a potential link between the crown-to-root ratio (CRR) and root morphology in patients with mild chronic periodontitis, which may be associated with tooth mobility. However, these findings have not been thoroughly investigated. Our previous study found that 76% of patients with aggressive periodontitis, particularly those with premolar involvement, exhibited abnormal root morphology, severe alveolar bone loss, and increased tooth mobility, leading to poor clinical outcomes. This study aims to investigate the specific correlations among alveolar bone resorption, root morphology, CRR, and periodontal clinical indicators with premolar mobility in stage III/IV grade C periodontitis patients aged ≤ 35 years. Materials and methods A total of 1,064 premolars from 151 stage III/IV grade C periodontitis patients aged ≤ 35 years were included in the study. Clinical periodontal parameters and radiographic measurements were recorded. Logistic regression analysis was used to explore the relationships between these indicators and tooth mobility. Results Significant variations in premolar root lengths were observed, ranging from 6.80 mm to 20.96 mm. Teeth with shorter roots (mean length: 10.22 mm) exhibited grade I mobility with only 28% alveolar bone resorption, whereas those with medium-length (mean length: 12.67 mm) and longer roots (mean length: 14.91 mm) exhibited mobility at 34% and 37% bone resorption, respectively. Regression models incorporating the bone-level CRR, average probing depth, and root length demonstrated strong predictive accuracy for tooth mobility (P < 0.001, AIC = 1700.574). Conclusion Premolar mobility is influenced by variations in root length, alveolar bone resorption, and probing depth. The bone-level CRR is an effective predictor for assessing tooth mobility, especially when there are differences in root length and alveolar bone resorption.